Overcoming emerging challenges in biocatalysis - Roura Padrosa, David (2020)
In the last few decades, biocatalysis has emerged as a promising path towards more cost-effective and sustainable chemical synthesis in the path of developing more environmentally friendly strategies. Biocatalysis offers a beneficial approach but its widespread application is hampered by the drawbacks associated with the use of enzymes; especially, their stability under industrial requirements and their reusability. New, more robust, biocatalysts have been identified from extremophiles and in parallel, protein immobilisation has advanced, permitting the reuse of the biocatalysts, facile separation from the reaction bulk and their application in continuous processes. In this work, several aspects linked to the use of biocatalysts in flow reactors have been investigated to solve relevant challenges and facilitate the application of biocatalytic methods for chemical synthesis. In this sense, a new method for the immobilisation of challenging enzymes has been developed and applied to a carboxylesterase for the hydrolytic deracemization of naproxen butyl ester in flow. Moreover, substrate insolubility has been resolved with the addition of surfactants (Chapter 4). Transaminases, and further optimization of their stability and applications, have also been investigated. Specifically, residues involved in PLP binding have been studied identifying a poorly conserved asparagine as a key amino acid in PLP stabilization in dimeric transaminases (Chapter 5). Novel synthetic methods involving transaminases have also been developed, specifically looking at the combination of a novel halo adapted alanine dehydrogenase to shift the equilibrium and reduce the amount of amino donor generally required (Chapter 6). Finally, the deamination of lysine was investigated for the synthesis of pipecolic acid. Here, the use of a transaminase was explored as well as a redox neutral cascade. This last system was co-immobilised in the same support and successfully applied in flow, achieving a volumetric yield of up to 2.5 g/h/L, 10-fold improvement from the fermentation-based production used up to date (Chapter 7).